Land Leveling Designs as Influenced by Soil Climate and Cropping Pattern - Arya, Y.C. (Journal of Soil and Water Conservation, 2022)
Land Leveling designs for providing an efficient agricultural production system are greatly influenced by soil, climate and cropping pattern associated with the land. Land leveling Plans, suitable for different agro-climatic zones are furnished. The design Cut to Fill ratio varies from 1.2 to 1.7 according to soil type, higher ratio being required for soils containing greater proportion of sand. Cuts as deep as 4 feet can be made in uniform soil profiles without any severe problems in crop production. Production rate of land leveling equipment is markedly influenced by moisture content of soil. In sandy loam soils containing 76% sand, production rate of towed scraper andwheel tractor combination can be increased by about 40% by leveling land after an irrigation than when dry.